History of the universalization of the Physical Culture in Guantanamo Municipality - Lourdes Ocaña-Charón (Universidad de Guantánamo, 2018)
The process of globalization of higher education is an essential part of the current battle of ideas waged by our people today in their determination to achieve a comprehensive general culture and to find concrete solutions to achieve greater equity and social justice. This work summarizes the history of development achieved by the university Branch of Physical Culture in the municipality Guantanamo, which provide the existence of a bibliographic material that may be used by students, teachers and everyone who wish to know about it. In recreate since its emergence of globalization as part of the battle of ideas results undergraduate, master's degrees, courses of excellence, operational quality, spelling diagnosis, management structures and its social impact. For its preparation methods and means of research workers, graduate students and community members were applied which allowed the incorporation of a set of information and statistical data. This research reveals the work of the National Institute of Physical Education (1928 1948), the Summer School of the University of Havana training of physical education teachers in the (1946), the National Institute of Sports, Physical Education and Recreation ( INDER) and the Ministry of Education (MINED), the National Subsystem Upgrade and Improvement for methodologists and Physical Education Teachers and the educational work of the Revolution with management and the greatness of the Commander in Chief Fidel Castro Ruz as part of the Battle of ideas.